Pengaruh Peningkatkan Produktivitas dengan Memperkenalkan Budaya Inklusif pada Pengelolaan Sumber Daya Manusia - Alifia Devis, Chinta; Arqy Ahmadi, Mirzam (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research aims to determine the impact of implementing an inclusive culture on increasing employee productivity from a human resource management perspective in a company. The problem behind this research is the importance of increasing the productivity of an organization which is often influenced by how human resources (HR) are managed. The following approach that is increasingly receiving attention is the implementation of an inclusive culture. Integrative culture is understood as a management approach process that respects individual diversity and fosters good and harmonious cooperation among all employees using research approaches and literature reviews. This research concludes that the implementation of an inclusive culture has a positive impact on employee productivity. Employees will feel appreciated and encouraged in an inclusive work environment and will have more motivation to contribute, which will ultimately result in maximum performance. This study can be taken into consideration so that a copany further strengthens its comprehensive program. The weakness in this research is that it is only based on available literature, thereby limiting the generalizability of the results. Because this research uses a literature review method, it is not possible to obtain the latest empirical data directly. Therefore, it is recommended that further research include more research with field studies and case studies that refer more to different industrial and geographical contexts.